Operationalising an integrated mortality transition framework for programmatic priority setting across maternal and newborn health - Allisyn C Moran; Ties Boerma; Gloria Ikilezi; Ryan Fitzgerald; Uzma Syed (BMJ Global Health)
Data-driven decision making will be instrumental in reducing maternal mortality, newborn mortality, and stillbirth levels in the coming years as the Sustainable Development Goal targets draw near in 2030. Tailoring evidence to be context-specific is crucial to target relevant questions, priorities, and needs. In doing so, there remains value in grounding local data in the broader global health data landscape. Here, we introduce one resource - an interactive benchmarking tool- that presents local insights contextualized in a maturity model based on evidence from over 150 countries. This tool positions a country in one of five mortality phases, compares its performance across maternal/newborn health program areas to peers in its phase, and facilitates connections to lessons from high-performing Exemplar countries that have achieved success on relevant indicators. It offers an opportunity to set evidence-based priorities, helping to identify indicators and subnational regions that may be important to target moving forward to accelerate progress. In select countries, the benchmarking approach has been piloted to inform maternal and newborn health evaluations and planning processes. This approach is adaptable to local contexts and use-cases, while in parallel fostering a shared way of thinking around maternal and newborn health strategic planning. In a global health financing environment that is increasingly constrained, such a tool to support data-driven priority setting is a timely resource.